CURRENT TUBERCULOSIS A IN HIV-INFECTED PATIENTS - Kholiev Bakhodir Oltibayevich (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Summary:             Tuberculosis is widespread in all regions of the world. According to WHO, in 2016, 476,774 people with tuberculosis had a positive HIV status, which accounted for 7.5% of all reported cases. In 2016, more than 374,000 people living with HIV died from  tuberculosis  worldwide  (WHO,  2017).  In  recent  years,  the In  the  Russian Federation, there is a steady increase in the incidence of tuberculosis in patients with HIV infection. According to the Federal Tuberculosis Monitoring Center, the number of people living with HIV infection has doubled. The article provides an overview of the  epidemic  indicators  of  tuberculosis  and  HIV  infection  in  Russia. Problems  of diagnosis of tuberculosis in combination withcoinfection, as well as new laboratory and  immunological  methods  used  today  in  the  world  and  domestic  practice  to determine tuberculosis infection.